Computational Studies of Some Hydrazone Derivatives as Antibacterial Agent: DFT and Docking Methods - Abel Oyebamiji; B. Benjamin Adeleke; Ajibade Adejoro; Oyedeji Folashade (Chemistry Department, The University of Brawijaya, 2019)
Quantum chemical calculations through density functional theory and docking study were carried out on a set of seven hydrazones and S. aureus cell line (4b19) so as to observe their inhibitory abilities of hydrazones. Many parameters which describe the anti-S. aureus were evaluated. All the compounds under study were docked against S. aureus cell line as receptors and the resulting binding energies reflected the extent of their binding affinities. 2,4-dinitrophenylhydrazone of formaldehyde showed the highest binding affinity.